Educational learning as a consequence of the COVID-19 pandemic. What role should the school play in the new world stage? - Sanz Ponce, Roberto; López-Luján, Elena (Revista Complutense de Educación, 2022)
The pandemic situation and school closures have a significant impact on teachers and students, which will have lasting consequences if timely educational policies and measures are not adopted. The objective of this article is to critically analyze some lessons that should be learned from this pandemic in reference to education, turning it into an opportunity to re-situate its meaning. The aspects to rethink -although there are others- are No student should be left out; Rationalizing the curriculum; New ways of working; and Resilient students and teachers. Among the conclusions are: the need to guarantee an effective right to education for all students, regardless of their abilities, needs or socioeconomic status. Educational policies and pedagogical practices must be implemented to reduce inequalities, learning gaps and promote equal opportunities; to end the rigidity of the system and of a curriculum that favors rote learning, oriented towards examination; to rethink the ways of teaching and learning, taking into account the proposals of neuropedagogy and active teaching; and, finally, the need to train resilient tutors capable of helping to overcome the consequences of COVID-19, in addition to strengthening this capacity among the teaching community itself.